Strategi Bisnis Umkm Ceriping Sebagai Transformasi Ekonomi Di Desa Kedungasri Kabupaten Kendal - Sabrina Al Azizah; Diana Anggun Oktavia; Lina Fauziyah; R. Rifda Adwitiya Sudarwin; Indah Nihayatur Romadhoniah; Lutfiyah (Lembaga Pengembangan Kinerja Dosen, 2024)
The ceriping MSMEs in Kedungasri Village, Kendal Regency, have played an important role in the transformation of the local economy. Through innovation and appropriate business strategies, these businesses have not only managed to maintain their production sustainability, but have also been able to grow in the face of increasingly competitive market challenges. Innovations include product diversification, application of simple technology in the production process, and improved packaging quality. Meanwhile, business strategies include strengthening marketing networks, utilizing digital platforms, and improving human resource skills. This transformation has had a significant impact on increasing community income and reducing the unemployment rate in Kedungasri Village, making the ceriping MSMEs the driving force of a sustainable village economy.